OUTCOME OF BURIED VERSUS EXPOSED KIRCHNER WIRES IN TERMS OF INFECTION IN FRACTURE OF PHALANGES AND METACARPAL BONE OF HAND - ANWAR, M; REHMAN, MU; ULLAH, N; BILAL, M; KHAN, M; RAFIULLAH, . (Biological and Clinical Sciences Research Journal, 2024)
Kirschner wire (K-wire) fixation is a common technique for treating phalangeal and metacarpal fractures due to its cost-effectiveness and efficiency. However, the risk of infection associated with exposed K-wires remains a significant concern. This study aimed to compare infection rates and clinical outcomes in hand fractures treated with buried versus exposed K-wires. Objective: To assess and compare infection rates, clinical interventions, and patient comfort between buried and exposed K-wires in phalangeal and metacarpal fractures. Method: This study was conducted at Bolan Medical Complex Hospital, Quetta, with 110 patients divided into two groups: Group A (55 patients with buried K-wires) and Group B (55 patients with exposed K-wires). Infection rates were evaluated by categorizing infections as superficial or deep. Clinical outcomes, including the need for antibiotics, K-wire removal, and patient comfort, were assessed for both groups. Results: Group A (buried K-wires) had significantly lower infection rates, with 3.6% of patients developing superficial infections and 1.8% deep infections. In contrast, Group B (exposed K-wires) had higher infection rates, with 10.9% experiencing superficial infections and 5.4% deep infections. Additionally, exposed K-wire patients required more clinical interventions, including increased antibiotic use and K-wire removal. Conclusion: Buried K-wires provide a safer and more comfortable alternative for hand fracture management, with significantly lower infection rates and reduced need for further medical intervention compared to exposed K-wires. Therefore, the use of buried K-wires is preferable for reducing infection risk and enhancing patient comfort.